Faktor Yang Memengaruhi Kejadian Dermatitis Kontak pada Petugas Pengangkut Sampah Di Tempat Pembuangan Akhir (TPA) Sampah Kota Tembilahan Tahun 2019 - Mitra; Salmariantity; M. Kamali Zaman (HEALTH CARE : JURNAL KESEHATAN, 2021)
Waste can not only disturb aesthetics or beauty, it can also cause flooding and health problems or diseases for humans. Skin disease is an occupational disease that is very often found. Based on the results of Riskesdas, 2007, dermatitis in Riau accounted for around 47.6% (percent) coming from waste management workers and in Indragiri Hilir accounted for 6.3% of dermatitis cases. This study aims to determine the Factors Affecting the Occurrence of Contact Dermatitis in Garbage Transport Officers at Tembilahan City Landfill. The type of research in this study is analytic with cross-sectional design. The population in this study were all garbage transport officers in Tembilhan City in 2018 as many as 294 people. Data analysis was performed univariate, bivariate and multivariate using multiple logistic regression tests. The results of the study found that garbage transporters with bad personal hygiene have a 4 chance of having contact dermatitis, contact time> 8 hours have a chance to experience contact dermatitis 3.86 times, age <31 years have a chance to experience contact dermatitis 41.78 times higher than age ≥ 31 years, female gender has the opportunity to experience contact dermatitis 2.78 times and there is a relationship between the use of PPE with the incidence of contact dermatitis (pvalue = 0.00). It is recommended from the results of this study to the garbage officer to always maintain personal hygiene, when to contact with garbage, and the right age in transporting waste so as not to contract contact dermatitis.